Teoria ator-rede e controvérsias no Twitter: cartografia da polêmica #nãoexisteestuproculposo - Andrade, Maria Beatriz Silva de (2023)
Digital platforms have played a significant role in the communicative articulation between human and non-human actors in digital social dynamics. Hate speech and misogynistic attacks have shaped the online world as yet another space for violence. Therefore, this research described the social around the term Rape Culposo through messages (tweets) associated with the hashtag #NãoExisteEstuproCulposo on the platform, Twitter. We use the theoretical framework of the Actor-Network Theory (LATOUR, 2012, 2007; LAW, 1999; CALLON, 1986) operationalized through the Cartography of Controversies (VENTURINI, 2010) to understand, from the Mariana Ferrer case, which are the discourses on the bodies and rape culture permeated and reverberated on the platform. Based on authors who think about gender violence (BUTLER, 2018), ideological bubbles, (SODRÉ, 2021), power and domination (BOURDIEU, 2012) and online platforming (DANDREA, 2020). In the results of the social cartography, it was possible to delineate the set of human and non-human actors, including actresses, singers, writers, soccer clubs and associations and organizations of civil society. The utterances and speeches were mapped and grouped into four main groups: Football, Racism and money, Machismo and patriarchy and Justice. In the analysis, we identified the controversies in the hashtags #mariferrermentiu and #mulherescomcostantino, where attacks on progressive press vehicles resided, blaming women and polarization between groups